2001
DOI: 10.1007/s004280100474
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profile of 22 pancreatic carcinoma cell lines

Abstract: The K-ras, p53, p16 and DPC4 genes are among those most frequently altered in pancreatic ductal carcinoma. We analyzed 22 cell lines for alterations in these genes by direct sequence analysis and methylation-specific polymerase chain reaction. These cell lines showed mutations in K-ras and p53 at frequencies of 91% and 95%, respectively. Alterations in p16INK4a were found in all cases and included nine homozygous deletions, seven mutations and promoter methylation in six cases. Eight cell lines (36%) had an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
274
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(287 citation statements)
references
References 27 publications
11
274
0
2
Order By: Relevance
“…GTP-bound Ras is able to bind and activate effector enzymes, therefore controlling cellular proliferation, survival and other aspects of cell behaviour that can contribute to the transformed phenotype. 9 It has been shown that reoviruses can take advantage of alterations in the Ras/PKR pathway, leading to lytic infection only in malignant cells but not in normal cells which they infect abortively. 10 Viruses that cannot reverse PKR activation by themselves would theoretically become, in this way, dependent on an active cellular Ras pathway for replication.…”
Section: Introductionmentioning
confidence: 99%
“…GTP-bound Ras is able to bind and activate effector enzymes, therefore controlling cellular proliferation, survival and other aspects of cell behaviour that can contribute to the transformed phenotype. 9 It has been shown that reoviruses can take advantage of alterations in the Ras/PKR pathway, leading to lytic infection only in malignant cells but not in normal cells which they infect abortively. 10 Viruses that cannot reverse PKR activation by themselves would theoretically become, in this way, dependent on an active cellular Ras pathway for replication.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of TGFh signaling in pancreatic cancer cells, the oncogenic Ras-Mek-ERK signaling cascade deserves particular attention because (a) activating K-Ras mutations are frequently found in pancreatic cancer and are also present in the pancreatic cancer cells used in this study (29)(30)(31), and (b) oncogenic K-Ras mutations frequently lead to constitutive activation of the downstream ERK-MAPK, which has been shown to be an effective antagonist of TGFh signaling (32). We therefore decided to study whether and how the Ras-Mek-ERK signaling pathway might interfere with TGFhinduced c-myc repression in pancreatic cancer cells.…”
Section: Inhibition Of Erk Restores Tgfb-induced Repression Of the Timentioning
confidence: 99%
“…Multiple mutations and changes in the expression of proto-oncogenes occur at a very high frequency in pancreatic cancer (Crnogorac-Jurcevic et al, 2001;Moore et al, 2001). Various oncogenes in signaling pathways have been indicated to contribute to drug resistance, including ras, protein kinase C, src, and so on (Masumoto and Nakano, 1997).…”
Section: Introductionmentioning
confidence: 99%